Protein Phosphatase 2A Reduces Cigarette Smoke–induced Cathepsin S and Loss of Lung Function - Doherty, Declan F.; Nath, Sridesh; Poon, Justin; Foronjy, Robert F.; Ohlmeyer, Michael; Dabo, Abdoulaye J.; Salathe, Matthias; Birrell, Mark; Belvisi, Maria; Baumlin, Nathalie; Kim, Michael D.; Weldon, Sinéad; et al. (American journal of respiratory and critical care medicine, 2019)
CTSS (cathepsin S) is a cysteine protease that is observed at higher concentrations in BAL fluid and plasma of subjects with chronic obstructive pulmonary disease (COPD). To investigate whether CTSS is involved in the pathogenesis of cigarette smoke-induced COPD and determine whether targeting upstream signaling could prevent the disease. CTSS expression was investigated in animal and human tissue and cell models of COPD. mice were exposed to long-term cigarette smoke and forced oscillation and expiratory measurements were recorded. Animals were administered chemical modulators of PP2A (protein phosphatase 2A) activity. Here we observed enhanced CTSS expression and activity in mouse lungs after exposure to cigarette smoke. mice were resistant to cigarette smoke-induced inflammation, airway hyperresponsiveness, airspace enlargements, and loss of lung function. CTSS expression was negatively regulated by PP2A in human bronchial epithelial cells isolated from healthy nonsmokers and COPD donors and in monocyte-derived macrophages. Modulating PP2A expression or activity, with silencer siRNA or a chemical inhibitor or activator, during acute smoke exposure in mice altered inflammatory responses and CTSS expression and activity in the lung. Enhancement of PP2A activity prevented chronic smoke-induced COPD in mice. Our study indicates that the decrease in PP2A activity that occurs in COPD contributes to elevated CTSS expression in the lungs and results in impaired lung function. Enhancing PP2A activity represents a feasible therapeutic approach to reduce CTSS activity and counter smoke-induced lung disease.